2018
DOI: 10.3390/nu10040430
|View full text |Cite
|
Sign up to set email alerts
|

New Statistical Approach to Apportion Dietary Sources of Iodine Intake: Findings from Kenya, Senegal and India

Abstract: Progress of national Universal Salt Iodization (USI) strategies is typically assessed by household coverage of adequately iodized salt and median urinary iodine concentration (UIC) in spot urine collections. However, household coverage does not inform on the iodized salt used in preparation of processed foods outside homes, nor does the total UIC reflect the portion of population iodine intake attributable to the USI strategy. This study used data from three population-representative surveys of women of reprod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The method of statistical analysis has been previously described ( 18 ) ; however, in brief, UNaC and salt iodine concentration (SI) were used as independent explanatory variables in multiple linear regression analyses with the UIC as the dependent variable. In our analysis, we used the natural logarithm of UIC to reduce the skew of the UIC distribution, and therefore the findings from UIC constituent analyses are geometric mean values.…”
Section: Methodsmentioning
confidence: 99%
“…The method of statistical analysis has been previously described ( 18 ) ; however, in brief, UNaC and salt iodine concentration (SI) were used as independent explanatory variables in multiple linear regression analyses with the UIC as the dependent variable. In our analysis, we used the natural logarithm of UIC to reduce the skew of the UIC distribution, and therefore the findings from UIC constituent analyses are geometric mean values.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, WHO recommends using urinary iodine concentration (UIC) for determining iodine status in populations. However, only using UIC to estimate the proportion of excessive iodine intake can be biased owing to high individual variability [ 5 ]. Recent investigations found that the combined use of urinary sodium concentration and UIC would alleviate the bias in evaluation of excessive iodine intake in population [ 5 ].…”
mentioning
confidence: 99%
“…However, only using UIC to estimate the proportion of excessive iodine intake can be biased owing to high individual variability [ 5 ]. Recent investigations found that the combined use of urinary sodium concentration and UIC would alleviate the bias in evaluation of excessive iodine intake in population [ 5 ]. Therefore, determining iodine status in current populations is insufficient; it is urgent to provide precise screening of individualized iodine status for different person.…”
mentioning
confidence: 99%